Air pollutants concentration and variation of blood glucose level among pregnant women in China: A cross-sectional study. (15th February 2020) - Li, Die; Wang, Jian-bing; Yu, Zhe-bin; Lin, Hong-bo; Chen, Kun
Abstract: Air pollution has been reported to be associated with the risk of type 2 diabetes, but no previous study has investigated the association with changes in blood glucose levels in pregnant women in China. We aimed to examine the associations of air pollution concentration with blood glucose among pregnant women. We identified 37, 383 women who were pregnant from hospital records from January 2013 to July 2017. We used generalized linear models to estimate adverse associations of air pollution on the glucose challenge test (GCT) and oral glucose tolerance test (OGTT) blood glucose levels among pregnant women in the second trimester on lag days 1–7, adjusting for a number of demographics, health and socioeconomic covariates. An IQR increase in PM2.5 concentration during the second trimester was associated with 2.09% (7-day lag, 95% CI: 1.62%, 2.57%) higher GCT blood glucose levels; the corresponding figures for PM10, NO2 and CO were 3.99% (7-day lag, 95% CI: 3.28%, 4.71%), 7.40% (6-day lag, 95% CI: 6.41%, 8.39%), and 4.23% (4-day lag, 95% CI: 3.75%, 4.71%), respectively. For PM2.5, PM10 and NO2 concentrations, significant associations were observed among women with older age, overweight/obesity, and lower education level. However, pregnant women with lower BMI were more susceptible to higher CO-related GCT blood glucose levels. Participants who worked as public servants and technicians may be less susceptible to the effects of PM2.5, PM10, NO2 and CO than women with the other three occupations considered. Too much or too little exercise frequency was susceptible to the adverse effects of air pollution in pregnant women (higher blood glucose levels). Our estimates for air pollutants and OGTT were generally consistent with the corresponding β values for GCT blood glucose. In the present study, women had higher blood glucose levels when exposed to higher residential PM2.5, PM10, NO2 and CO during their pregnancy. Women with higher BMI and lower education levels were more susceptible to the adverse effects of ambient air pollution. Highlights: We examined the effects of exposure to air pollution on blood glucose in pregnant women in a cross-sectional study. Women were at increased risk for higher blood glucose level when exposure to higher residential PM2.5, PM10, NO2 and CO during their pregnancy. Women with higher BMI, lower education level were more susceptible to the adverse effects of ambient air pollution. Non-linearity was observed in PM, NO2, CO related blood glucose variation.